2022
DOI: 10.1108/mhsi-12-2021-0085
|View full text |Cite
|
Sign up to set email alerts
|

A systematic scoping review of interventions delivered by peers tosupport the resettlement of refugees and asylum seekers

Abstract: Purpose The purpose of this study is to conduct a systematic search of the literature as it pertains to interventions delivered by peers to refugees and asylum seekers during the resettlement process. Design/methodology/approach A preferred reporting items for systematic reviews and meta-analysis-compliant scoping review based on Arskey and O’Malley’s (2006) five steps was used. Four databases, Scopus, Embase, Ebsco and ScienceDirect, were searched for peer-reviewed articles published in English from 2000 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…While meta-analyses provide evidence of peer support across mental health and substance use [ 78 , 79 , 80 ] there is a paucity of research in the extant literature as it relates to peer support from a trauma perspective specifically. Although two papers do provide initial insights into the role peers can play in supporting people with trauma [ 81 , 82 ] much more research needs to be done in this arena, if peer support is to be included in organizational responses as part of TIC.…”
Section: Discussionmentioning
confidence: 99%
“…While meta-analyses provide evidence of peer support across mental health and substance use [ 78 , 79 , 80 ] there is a paucity of research in the extant literature as it relates to peer support from a trauma perspective specifically. Although two papers do provide initial insights into the role peers can play in supporting people with trauma [ 81 , 82 ] much more research needs to be done in this arena, if peer support is to be included in organizational responses as part of TIC.…”
Section: Discussionmentioning
confidence: 99%
“…Successful peer leadership for those with mental health issues has a good evidence base of supporting well-being (Hardy et al , 2019). For example, Mahon (2022) in his systematic scoping review found that interventions for refugees facilitated by refugee peer leaders reduced psychological distress, and Stewart et al (2018) noted peer support reduced loneliness and isolation and improved the ability to cope. In addition, Huang et al (2020) reviewed ten randomised control trials and found that peer support was helpful in reducing depression in mothers during the perinatal time.…”
Section: Introductionmentioning
confidence: 99%